PENERAPAN MODEL PEMBELAJARAN KOOEPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SEKOLAH DASAR - Samsur (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
This research is motivated by the lack of IPS student learning outcomes can be seen from the results of the students' social studies class V SD Negeri 54 Sebangar with an average value of 60.65. Therefore, the researchers provide an alternative implementation strategies in the classroom to the application of learning models kooeperatif make a match type in the class V SD Negeri 54 Sebangar in the academic year 2014/2015. This research aims to improve learning outcomes IPS V grade students of SD Negeri 54 Sebangar with the application of learning models kooeperatif make a match type in the class V Implementation Strategy. Form of research is the Classroom Action Research (PTK) with 2 cycles. Based on research data anlisis after applying of learning models kooeperatif make a match type, the average percentage of the activity of teachers in the first cycle 74.99% increased to 91.06% in the second cycle. The average percentage of student activity also increased, namely 67.85% in the first cycle increased to 82.14% in the second cycle. Student learning outcomes in basic score by the average value of 60.65 and the first cycle increased with an average value of 75.00 class with a 23.66% increase in the percentage of learning outcomes and the percentage of students who completed 84.61%, and the second cycle increased again by an average of 82.30 with the percentage improvement classlearning outcomes 35.69% and the percentage of students who completed 88.46%. These results indicate that the application the application of learning models kooeperatif make a match type in the class V IPS grade students of SD Negeri 54 Sebangar.